Australia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews developments in the Australian economy during 1994-95. In 1994/95, real GDP grew by 4 1\2 percent as growth in domestic demand accelerated sharply, rising by 6 3/4 percent, despite the impact of a severe drought on farm output. Business investment increased by 17 1\2 percent with investment in plant and equipment rising by 21 1\2 percent and that in nonresidential construction by 7 3/4 percent. Private consumption growth also rose strongly, by 5 percent, reflecting strong growth in employment and some acceleration in wage growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet